Social health behavior in patient sith diabetes The diabetes center in Lattakia is a model (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
the aim of the research is to identigy the health and social behavior of patients with chronic diabetes in the diabetes center of lattak, The research Sample consisted of (10) people with diabetes, The interview was conducted with asample, The descriptive analytical method was to study and reality of phenomenon, The researcher reached the following results: there are differences in the health and social behavior of patients with chronic diabetes depending on variable of age, gendre and place of residence.Search Keywords: Social health behavior, the health, the disease, chronic diseases, Diabetics.